Cypraea in Miocene bryoide from surroundings of Mlinše near Izlake, Slovenia - Mikuž, Vasja; Pavšič, Jernej (Geologija, 2001)
Considered is an example of bryoide from the surroundings of Mlinše near Izlake, Slovenia, on stone core of a Miocene snail from the group of cowries (Cypraeidae). Bryoids have not been known hitherto in Slovenia, and nomination of such bryozoan structures and laminar overgrowths has not been practiced with us yet.